CFD analysis of convergent-divergent nozzle flow and base pressure control using micro-JETS - Khan, Ambareen; Abid, Abdul; Khan, Sher Afghan (Science Publishing Corporation, 2018)
This paper presents numerical study was undertaken to identify the use of the micro-jets to regulate the pressure in the region from two-dimensional convergent-divergent (CD) Nozzle. At the exit of the divergent nozzle in the base region 1 mm of two micro-jets orifice diameter has been arranged at ninety degrees at pcd 13 mm to control base pressure. The inertia level at the inlet to suddenly expanded duct was 1.87. The micro-jets are suddenly expanded into a two-dimensional planar area ratio of 3.24. The L/D of the duct was 1, 2, 4, 5, 6, 8 and 10. The total wall pressure distribution from inlet to the outlet too was recorded. The results indicate that the micro-jets can oblige as the effective regulators of the pressure in the base area. The duct wall pressure field is not negatively affected by the dynamic control. Nozzles were operated with the NPR in the range from 3 to 11. The results show that we can fix the flow parameter which will result in the maximum gain in the base pressure, velocity and temperature. The convergent-divergent nozzle geometry has been modeled and sim-ulated employing turbulence models: K-ε standard wall function turbulence model from the code was validated with the commercial com-putational fluid dynamics.